Observation of the Λb0→Λ+cK+K−π− decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2021)
The Λb0→Λc+K+K−π− decay is observed for the first time using a data sample of proton-proton collisions at centre-of-mass energies of s=7 and 8TeV collected by the LHCb detector, corresponding to an integrated luminosity of 3fb−1. The ratio of branching fractions between the Λb0→Λc+K+K−π− and the Λb0→Λc+Ds− decays is measured to beB(Λb0→Λc+K+K−π−)B(Λb0→Λc+Ds−)=(9.26±0.29±0.46±0.26)×10−2, where the first uncertainty is statistical, the second systematic and the third is due to the knowledge of the Ds−→K+K−π− branching fraction. No structure on the invariant mass distribution of the Λc+K+ system is found, consistent with no open-charm pentaquark signature.